Laser Guide Star uplink beam: scattering and Raman emission measurements with the 10.4m Gran Telescopio CANARIAS. Issue 1 (6th August 2022) - Lombardi, G; Bonaccini Calia, D; Centrone, M; de Ugarte Postigo, A; Geier, S
ABSTRACT: Laser Guide Star Adaptive Optics (LGS-AO) is becoming routine in several astronomical observatories. The use of powerful lasers generates sensible Raman emissions on the uplink laser beam path, plus secondary Rayleigh scattering from atmospheric molecules and Mie scattering from aerosols. This paper reports the results of a campaign done with the 10.4m Gran Telescopio CANARIAS (GTC); this campaign was undertaken to assess the spectral and photometric contamination coming from a 589 nm laser uplink beam scattering and Raman emission induced on the GTC spectro-imager OSIRIS by laser launched ∼1 km off-axis. The photometric contamination is due to primary and secondary scattering of the uplink photons, as well by the Raman inelastic scattering. We have propagated the laser beam creating a mesospheric LGS, then pointed and focused the GTC telescope towards the uplink laser beam, at different heights and up to the LGS, taking into account the observing geometry. In our observations, the Raman emissions for O2 and N2 vibrational lines are visible at 20 km, weakening with altitude and becoming undetectable above 30 km. The scattering of the focused uplink beam is detectable at less than ±0.2 arcmin from the centre of the beam, while for the focused LGS the scattering is narrower, being detectable at less than ±0.1 arcmin around the plume. Recommendations for Laser Traffic Control Systems are given accordingly.